Endo and ectoparasites in conventionally maintained rodents laboratory animals - Medeiros, Vítor Brasil (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2012)
Purpose: One of the most common problems regarding the health conditions of laboratory animals has been the endo and ectoparasites. The aim of this review is to discuss the most important aspects of these disorders in research rodents. Methods: The author performed a review in Pubmed, SieLo and Web of Science using the key words: parasites, rodents, laboratory animals, endoparasites and ectoparasites. The most relevant and recent articles were reviewed and used to elaborate this paper. Isues about clinical simptoms, diagnosis, prophylaxis and treatment of the most frequent protozoa, helminths and ectoparasites in laboratory rodents were analysed. Conclusion: This review demonstrates that endo and ectoparasites are common in laboratory rodents, and that veterinary control is essential to get quality control, welfare and health of research animals.